Modelling marine turbine arrays in tidal flows - Stansby, Peter K.; Ouro, Pablo (Journal of hydraulic research, 2022)
Tidal stream turbines operate in the harsh marine environment, subjected to turbulence, wave action and wakes from upstream devices when deployed in arrays. Turbines may be mounted on the sea bed or on floating platforms. Numerical models are invaluable to study individual and array performance and their interaction with environmental flows. To date, shallow water models and three-dimensional Reynolds averaged Navier-Stokes (RANS) simulations predominate the simulation of turbine arrays, while large-eddy simulation (LES) is becoming more widely used due to availability of high-performance computing resources. The accuracy of turbine performance and load prediction depends on the ability to represent turbulence in the tidal flow and unsteady wake effects. Inclusion of waves increases the modelling complexity and is particularly significant for floating platforms. In this Vision Paper, we provide a perspective on the numerical approaches currently used for modelling tidal flows and marine turbines, suggesting future challenges envisaged in this field.